Mekanisme Keracunan Saraf Akibat Konsumsi Kerang-kerangan yang Terkontaminasi Dinoflagellata Beracun (Studi Literatur) - Sari Sudarmiati; Badrus Zaman (Department of Nursing, Faculty of Medicine, Diponegoro University, 2010)
Dinoflagellata is a micro algae where live in water habitat and about 30 species can produce poison material called “sax toxin”. Organic water pollution is one of a stimulant agent blooming algae that is caused by nutrient abundance. Poison mobility from marine organisms to human body usually pass through food chain mechanism, where human ingestion contaminated shellfish by toxin Dinoflagellata that produce sax toxin. It’s toxin can be attack nerves membrane then rise of paralytic. This virulence caused by bounding of conducive nerves trait. Saxitoxin is poison where can be a block agent function to exclude Na+ into nerve membrane. Death rate by paralytic cases gain to 20% of human exposure.